Building capacity to link agriculture and nutrition - Babu, Suresh Chandra (International Food Policy Research Institute, 2019)
This chapter focuses on how building and strengthening capacity at the individual and institutional levels can in turn strengthen agriculture– nutrition linkages. It focuses on two specific aspects of capacity. First, it highlights ways in which universities, organizations, and governments are working to improve cross-sectoral educational opportunities for students. Second, it explores how extension and agricultural services could be made more nutrition-sensitive by improving their content or the capacity of extension workers through formal education and training, in turn improving farmers’ understanding of agriculture–nutrition linkages within production, on-farm processing, storage, and marketing; and consumers’ purchasing decisions (FAO, 2014). Finally, it reflects on lessons that can be learned from efforts to increase capacity at these critical levels.